POWER RELATIONS AND ACCESS TO NATURAL RESOURCES: A COMPARATIVE STUDY OF ECOLOGICAL CONFLICTS IN NATIONAL STRATEGIC PROJECTS IN INDONESIA (ANDESITE MINE IN WADAS VILLAGE AND ECO-CITY IN REMPANG ISLAND 2017-2024) - Muhammad Asdin Asri; Riaty Raffiudin (RADJA PUBLIKA, 2026)
This study analyzes ecological conflicts within the framework of the National Strategic Project (PSN) in Wadas Village (Central Java) and Rempang Island (Riau Islands) using the access theory developed by Jesse Ribot and Nancy Peluso (2003). This theory views access as the ability of actors to obtain benefits from natural resources through legal and non-legal mechanisms, such as power, capital, discourse, and social networks. This approach is used to understand the competition between the state, corporations, and local communities in controlling and utilizing natural resources in the context of national development. This study uses a qualitative research method with a comparative political studies approach. Data were obtained through a review of literature, policy documents, advocacy organization reports, and media coverage relevant to the conflict dynamics in both regions. The research findings show that the conflicts in Wadas and Rempang share structural similarities, both rooted in the development of National Strategic Projects that legitimize the expansion of access to natural resources by powerful state and private actors. Powerful actors utilize a combination of legal access, political authority, and development discourse to open up space for development and investment interests. Nevertheless, communities demonstrate collective resistance rooted in ecological, social, and cultural claims. The main differences lie in the nature of the resources and the mechanisms of exclusion. The Wadas conflict is prominent in its ecological-agrarian dimension due to andesite mining that threatens agricultural land and water sources, while the Rempang conflict is more focused on the economic-political and cultural dimensions resulting from the relocation of communities from coastal areas for industrialization projects. Thus, ecological conflicts in Indonesia are a manifestation of the politics of access, namely the struggle between actors for the ability to benefit from natural resources under the hegemony of national development.